Peningkatan Keaktifan dan Hasil Belajar Siswa Melalui Model Pembelajaran Problem Based Learning (PBL) Berbantuan Media Teka-Teki Silang pada Materi Kaidah Kebahasaan Teks Biografi di Kelas X SMA N 2 Medan - Hernita Simatupang; Rita (STKIP Subang, 2025)
This study seeks to evaluate the impact of the Problem Based Learning (PBL) model utilising crossword puzzle media on students' academic performance and comprehension of the linguistic conventions of biographical texts among grade X students at SMA N 2 Medan. The employed methodology is Classroom Action Research (CAR), structured in cycles that encompass preparation, implementation, observation, and reflection. Quantitative data indicate a substantial rise in students' pre-test and scores, whilst qualitative data from observations and questionnaires corroborate an enhancement in student and instructor engagement and interaction. The findings demonstrate that employing the PBL paradigm alongside crossword puzzle media effectively enhances learning outcomes and student comprehension of the subject, therefore serving as an innovative alternative in the Indonesian language education process.